Serum Concentrations of Symmetric Dimethylarginine and Creatinine in Dogs with Naturally Occurring Chronic Kidney Disease - Hall, J. A.; Yerramilli, M.; Obare, E.; Yerramilli, M.; Almes, Kelli; Jewell, D. E. (My University, 2016)
Background: Serum concentrations of symmetric dimethylarginine (SDMA) detected chronic kidney disease (CKD) in cats an average of 17.0 months before serum creatinine (Cr) concentrations increased above the reference interval. Objectives: To report on the utility of measuring serum SDMA concentrations in dogs for detection of CKD before diagnosis by measurement of serum Cr. Animals: CKD dogs (n = 19) included those persistently azotemic for ?3 months (n = 5), dogs that were azotemic at the time of death (n = 4), and nonazotemic dogs (n = 10). CKD dogs were compared with healthy control dogs (n = 20). Methods: Retrospective study, whereby serum Cr concentrations were determined by enzymatic colorimetry and serum SDMA concentrations were determined by liquid chromatography-mass spectrometry in dogs with necropsy confirmed CKD. Results: Serum SDMA increased before serum Cr in 17 of 19 dogs (mean, 9.8 months; range, 2.2-27.0 months). Duration of elevations in serum SDMA concentrations before the dog developed azotemia (N = 1) or before the dog died (N = 1) was not determined. Serum SDMA and Cr concentrations were linearly related (r = 0.84; P < .001). Serum SDMA (r = -0.80) and serum Cr (r = -0.89) concentrations were significantly related to glomerular filtration rate (both P < .001). Conclusion and Clinical Importance: Using serum SDMA as a biomarker for CKD allows earlier detection of kidney dysfunction in dogs than does measurement of serum Cr. Earlier detection might be desirable for initiating renoprotective interventions that slow progression of kidney disease. © 2016 American College of Veterinary Internal Medicine.
Citation: Hall, J. A., Yerramilli, M., Obare, E., Yerramilli, M., Almes, K., & Jewell, D. E. (2016). Serum Concentrations of Symmetric Dimethylarginine and Creatinine in Dogs with Naturally Occurring Chronic Kidney Disease. Journal of Veterinary Internal Medicine, 30(3), 794-802. doi:10.1111/jvim.13942
Keywords: Canine; Endogenous; Pet Foods; Predictor